Pelatihan Handicraft Bagi Santri Dayah Misbahul Huda - Rizayanti; Sonia Ulfa (BA: Jurnal Pengabdian kepada Masyarakat, 2024)
The Handicraft Training for santri at Dayah Misbahul Huda in Gampong Beusa Meurano, Peureulak Subdistrict, East Aceh Regency aims to enhance the skills, creativity, and economic independence of the santri through the creation of handcrafted products. This program is designed to introduce practical skills that support entrepreneurship and provide additional income sources for the students. The training methods used include lectures, demonstrations, hands-on practice, and evaluations. The results of this training show an improvement in basic handicraft skills, creativity in design, and an increased interest in entrepreneurship among participants. Additionally, the program opens up the potential for the establishment of craft-based businesses within the pesantren. This training contributes positively to the economic empowerment and independence of the santri, while enriching their experience in managing creative businesses.